Real time model validation and control of DC motor using matlab and USB - Mohammed Salih, Mohammed Farooq (2014)
Mechatronics system needs motion or action of some sort. It is created by a force or torque that results in acceleration and displacement. To produce this motion or action, actuators are the device being used. There are many types of actuators and one of the common types of electromechanical actuators is the direct current (DC) motor. The main goal of this project is to estimate the actual model of DC motor and control its speed using an embedded system interfaced to computer. The model identification is achieved using simple and low cost data acquisition system. An Arduino Uno embedded board system is used to collect the data from the sensors, send it to the computer, and control the model. The data processing is performed using MATLAB/SIMULINK. The validation for both the model and the controller are verified through simulations and experiments. The identification and the controllers results were coherent and successful